Implementation of Collaborative Learning in Improving Teachers' Social Competence (Case Study of Teachers of SMPN 2 Darangdan Purwakarta) - Rina Supriati; Neneng Halimah; Suharyanto Soro; Nana Herdiana Abdul Rahman (Global Education Journal, 2025)
The lack of teachers' social competence has a negative impact on the decline of the image of a pleasant school environment. The purpose of this research is to find and analyze the implementation of collaborative learning that can improve the social competence of teachers of SMP Negeri 2 Darangdan Purwakarta. This research uses a case study approach. The data collection method used participatory observation, in-depth interviews, and documentation studies on learning community activities. The results of the study show that (1) Collaborative learning that is institutionalized through the forum of Learning Communities (Kombel) and Lesson Study can change the work pattern of teachers that were originally individualistic to more collective; (2) The interaction process in planning and evaluating joint learning significantly hones communication skills, cooperation, and empathy between peers; (3) The main obstacles found were time constraints and schedule adjustments, but the managerial support of the principal was the key to the success of the program. The conclusion of this study is that effective collaborative learning functions as a social laboratory that matures teachers' professional attitudes.